2005
DOI: 10.1007/s11177-005-0152-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Effects Induced by Nickel Sulfate in Germline and Somatic Cells of WR Mice

Abstract: We examined the effects of nickel sulfate at doses 0.5 to 5.0 mg/kg (1/200-1/20 LD 50 ) on the frequency of dominant lethal mutations and double-strand DNA breaks (DSBs) in germline cells and on an increase in frequency in gene mutations W y in pigment cells of first-generation mice. The results indicated that spermatogenesis stages most sensitive to nickel sulfate (at a dose of 1.0 mg/kg) are spermatozoids, early spermatids, late spermatocytes, and stem spermatogonia. No statistically significant increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Subcutaneous injections of nickel sulfate to rats caused hyperemia of testicular intertubullar capillaries, disintegration of spermatozoa, and inhibition of spermatogenesis, depending on the dose [141,142]. Domshlak et al [143] found that in mice spermatozoids, early spermatids, late spermatocytes, and stem spermatogonia are most sensitive to nickel sulfate. On the other hand, nickel deprivation also reduced the rat reproductive performance by decreasing sperm production rate and spermatozoa motility.…”
Section: Reproductive System and Embryotoxicitymentioning
confidence: 99%
“…Subcutaneous injections of nickel sulfate to rats caused hyperemia of testicular intertubullar capillaries, disintegration of spermatozoa, and inhibition of spermatogenesis, depending on the dose [141,142]. Domshlak et al [143] found that in mice spermatozoids, early spermatids, late spermatocytes, and stem spermatogonia are most sensitive to nickel sulfate. On the other hand, nickel deprivation also reduced the rat reproductive performance by decreasing sperm production rate and spermatozoa motility.…”
Section: Reproductive System and Embryotoxicitymentioning
confidence: 99%
“…Some researchers and toxicologists are focusing on the risk of environmental pollution by heavy metals, which are dangerous and cause effects related to animal studies, toxic effects due to oral exposure, with the possibility of slow development (Domshlak et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that testicular toxicity of nickel compounds may be related to enhanced production of reactive oxygen species, probably mediated through oxidative damage to macromolecules, including damage of DNA. Lindemann et al [11] investigated a selective effect of Ni 2+ on wave initiation in bull spermatozoa flagella. Although spontaneous coordination of flagellum waves is lost after exposure to Ni 2+ , other function of the flagellum remain intact.…”
Section: Resultsmentioning
confidence: 99%